Response of Methanogenic Microbial Communities to Desiccation Stress in Flooded and Rain-Fed Paddy Soil from Thailand - Reim, Andreas; Hernández, Marcela; Klose, Melanie; Chidthaisong, Amnat; Yuttitham, Monthira; Conrad, Ralf (Frontiers in Microbiology, 2017)
Rice paddies in central Thailand are flooded either by irrigation (irrigated rice) or by rain (rain-fed rice). The paddy soils and their microbial communities thus experience permanent or arbitrary submergence, respectively. Since methane production depends on anaerobic conditions, we hypothesized that structure and function of the methanogenic microbial communities are different in irrigated and rain-fed paddies and react differently upon desiccation stress. We determined rates and relative proportions of hydrogenotrophic and aceticlastic methanogenesis before and after short-term drying of soil samples from replicate fields. The methanogenic pathway was determined by analyzing concentrations and δ13C of organic carbon and of CH4 and CO2 produced in the presence and absence of methyl fluoride, an inhibitor of aceticlastic methanogenesis. We also determined the abundance (qPCR) of genes and transcripts of bacterial 16S rRNA, archaeal 16S rRNA and methanogenic mcrA (coding for a subunit of the methyl coenzyme M reductase) and the composition of these microbial communities by T-RFLP fingerprinting and/or Illumina deep sequencing. The abundances of genes and transcripts were similar in irrigated and rain-fed paddy soil. They also did not change much upon desiccation and rewetting, except the transcripts of mcrA, which increased by more than two orders of magnitude. In parallel, rates of CH4 production also increased, in rain-fed soil more than in irrigated soil. The contribution of hydrogenotrophic methanogenesis increased in rain-fed soil and became similar to that in irrigated soil. However, the relative microbial community composition on higher taxonomic levels was similar between irrigated and rain-fed soil. On the other hand, desiccation and subsequent anaerobic reincubation resulted in systematic changes in the composition of microbial communities for both Archaea and Bacteria. It is noteworthy that differences in the community composition were mostly detected on the level of operational taxonomic units (OTUs; 97% sequence similarity). The treatments resulted in change of the relative abundance of several archaeal OTUs. Some OTUs of Methanobacterium, Methanosaeta, Methanosarcina, Methanocella and Methanomassiliicoccus increased, while some of Methanolinea and Methanosaeta decreased. Bacterial OTUs within Firmicutes, Cyanobacteria, Planctomycetes and Deltaproteobacteria increased, while OTUs within other proteobacterial classes decreased.